COMMUNITY EMPOWERMENT FOR PREVENTION AND SCREENING OF COVID-19 COMORBID DISEASE IN AYAPO VILLAGE - Frengky Apay; Ardhanari Hendra Kusuma; Rohmani Rohmani (Caring : Jurnal Pengabdian Masyarakat, 2022)
Public awareness in facing the Corona Virus Disease-19 (Covid-19) pandemic is decreasing, many are neglecting the use of masks, keeping a safe distance of 1-2 meters, washing hands with soap and the use of hand sanitizers has also decreased. This shows that the fact that the incidence of covid-19 cases is increasing. The surge in Covid-19 patients is still not under control by many countries, but some of them have experienced a decline. After almost recording 100,000 new Covid-19 patients in a day. Awareness in preventing covid-19 by implementing public health protocols is decreasing. Therefore, it is necessary to have the involvement of village community leaders, religious leaders, youth leaders, women leaders, youth coral cadets, heads of community health centers and local governments to make the village community aware. We will form a covid-19 task force team in Ayapo Village. The examination of Comorbid Diseases by screening blood pressure measurements, measuring cholesterol levels, and measuring uric acid levels in adult patients in Ayapo Village The purpose of this community service is to prevent the spread of Corona virus disease-19 in Ayapo Village. This community service method is with a quantitative approach by providing health counseling to the community, screening for comorbid corona virus disease-19. The results showed that the knowledge of the people of Ayapo village about Corona virus disease- 19 was most dominant knowledge with a total of 58 people (81.7%) and the least was good knowledge totaling 2 people (2.8%). Conclusion: Community knowledge and public awareness in preventing covid-19 in Ayapo Village are still lacking.